11.27 Understanding variability in UK acute neurology services: what works, and what doesn't?. Issue 12 (14th November 2019) - Best, Jonathan; Kamourieh, Salwa; Mummery, Cath
Abstract : Background: The 2017 ABN Acute Neurology Survey showed acute neurological services in the United Kingdom to vary widely, even between otherwise-similar departments. Focussing on positive outliers, we conducted qualitative research to understand this. Methods: Through the 2017 survey, we identified DGHs and neurology/neuroscience centres which indicated high overall acute neurology service provision or outstanding performance in a particular area. From 39 hospitals meeting our criteria, we asked 15 clinical leads from throughout the UK to complete a questionnaire on their service model and development. We also analysed free text comments from the 2017 survey. Results: We received 9 responses, 6 from DGHs. Successful innovations included a neurology take, seven-day consultant-delivered reviews, and an 'acute neurologist of the week'. Respondents viewed a well-functioning acute clinic as important, and we profiled how this was achieved. In DGHs, acute care was mainly delivered by consultants, who described heavy workloads. Of 120 comments from the 2017 survey, 37.5% described acute clinic arrangements. Overbooking of urgent patients into routine clinics was common. After this, the most frequent themes were understaffing (13.3%) and excessive workload (10%). Discussion: Our qualitative data identifies difficulties facing UK acute neurologists, and highlights successful approaches which may inform future service development.